2015
DOI: 10.1007/s00403-015-1607-6
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell tryptase and chymase in the progress of cutaneous vasculitis

Abstract: In animal models of vasculitis, mast cells are essential in the pathogenesis, but their involvement in human skin vasculitis is obscure. Because tryptase and chymase are potent serine proteinases in the secretory granules of mast cells, the purpose was to examine the number of mast cells expressing tryptase and chymase during the progress of cutaneous vasculitis. These numbers were correlated with the appearance of immunoreactants (C3c, fibrin, IgM, IgA and IgG) in vessel walls. For this, skin biopsies were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Tryptases are secreted in active form (bound to heparan sulfate) and can act either directly on endothelial cells or indirectly on ECM to induce angiogenesis in tumors . Beside their role in angiogenesis, MCs play important role in inflammation and can transition from a protective immune cells to a potent pro‐inflammatory cells which have a significant impact on the progression of many autoimmune conditions, such as inflammatory bowel disease, insulin‐dependent diabetes mellitus, rheumatoid arthritis, psoriasis, multiple sclerosis, bullous pemphigoid, chronic idiopathic urticarial, systemic lupus erythematosus, and cutaneous vasculitis . Tryptase can induce inflammation by stimulating the endothelial cells to release inflammatory mediators such as IL‐6, IL‐1, IL‐8, SCF, and TNF‐α, as well as promoting the chemotaxis of inflammatory cells such as neutrophils and macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…Tryptases are secreted in active form (bound to heparan sulfate) and can act either directly on endothelial cells or indirectly on ECM to induce angiogenesis in tumors . Beside their role in angiogenesis, MCs play important role in inflammation and can transition from a protective immune cells to a potent pro‐inflammatory cells which have a significant impact on the progression of many autoimmune conditions, such as inflammatory bowel disease, insulin‐dependent diabetes mellitus, rheumatoid arthritis, psoriasis, multiple sclerosis, bullous pemphigoid, chronic idiopathic urticarial, systemic lupus erythematosus, and cutaneous vasculitis . Tryptase can induce inflammation by stimulating the endothelial cells to release inflammatory mediators such as IL‐6, IL‐1, IL‐8, SCF, and TNF‐α, as well as promoting the chemotaxis of inflammatory cells such as neutrophils and macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…The role of mast cells in the etiology of CNS vasculitis (CNSV) remains controversial. While some groups have suggested protective roles of those cells in large vessel vasculitis via histamine-dependent repression of pro-inflammatory IL- (Springer, et al, 2017), others have suggested that hyperactivated mastocytes contribute to inflammatory-dependent deterioration of blood vessels (Kiely, et al, 1997;Lipitsa, et al, 2015). Kiely and colleagues reported a role for mast cells in the genesis of mercuric chloride-induced vasculitis in Brown Norway rats (Kiely, et al, 1997).…”
Section: Mast Cells and Central Nervous System Vasculitismentioning
confidence: 99%
“…Patients with other skin diseases (n = 21) recruited at the same reference center were diagnosed based on histopathology: nonspecific chronic inflammatory process (n = 3), chromomycosis (n = 1), cutaneous leishmaniasis (n = 3), paracoccidioidomycosis (n = 3), herpes (1), lichen planus (2) granuloma annulare (3), scleroderma (2) vitiligo (3).…”
Section: Study Groupsmentioning
confidence: 99%
“…Besides allergic responses, MCs play a much broader role in cutaneous inflammatory and non-inflammatory diseases promoting or suppressing inflammation. In normal skin, mast cells accumulate in the upper dermal region, around vessels, nerves and appendages [3], and are abundant in organs exposed to the environment like the respiratory and gastrointestinal tracts and the skin [4,5]. The location of mast cells in the dermal layer of the skin allows a quick response to injury [6].…”
Section: Introductionmentioning
confidence: 99%